2005
DOI: 10.1256/qj.04.54
|View full text |Cite
|
Sign up to set email alerts
|

Balanced tropical data assimilation based on a study of equatorial waves in ECMWF short-range forecast errors

Abstract: SUMMARYThis paper seeks to represent the tropical short-range forecast error covariances of the European Centre for Medium-Range Weather Forecasts (ECMWF) model in terms of equatorial waves. The motivation for undertaking this investigation is increasing observational evidence indicating that a substantial fraction of the tropical largescale variability can be explained by equatorially trapped wave solutions known from shallow-water theory. Shortrange forecast differences from a data-assimilation ensemble were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 33 publications
2
53
0
Order By: Relevance
“…In particular, low values are found in the Tropics and in data-rich areas (North America, Europe, Asia), whereas much higher values are observed in data-poor areas (such as over sea) and in the storm-track regions (Northern/Southern Atlantic, Northern/Southern Pacific). Another interesting point is the frequent occurrence of relatively large errors along the intertropical convergence zone (ITCZ), which is in accordance with the results of Zagar et al (2005) for the error in the zonal wind field.…”
Section: Dynamics Of the Standard Deviation Fieldsupporting
confidence: 81%
“…In particular, low values are found in the Tropics and in data-rich areas (North America, Europe, Asia), whereas much higher values are observed in data-poor areas (such as over sea) and in the storm-track regions (Northern/Southern Atlantic, Northern/Southern Pacific). Another interesting point is the frequent occurrence of relatively large errors along the intertropical convergence zone (ITCZ), which is in accordance with the results of Zagar et al (2005) for the error in the zonal wind field.…”
Section: Dynamics Of the Standard Deviation Fieldsupporting
confidence: 81%
“…The wind field is poorly recovered, with correlations below 0.2 in many areas. Previous studies (e.g., Parrish and Derber 1992; Zagar et al 2005) have shown that a tropical pressure observation makes little change to the tropical wind first guess and, therefore, has little impact on the tropical wind analysis. In contrast, we find that the ensemble filter can produce a substantial covariance between the first-guess surface pressure and tropical wind fields, resulting in modifications to the first-guess tropical wind field that are on the same order (0.5-1 m s _1 ) as in the midlatitudes.…”
Section: Influence Of a Single Pressure Observation On The Resulting mentioning
confidence: 96%
“…Again, the averaging may be carried out instantaneously over the N − 1 pairs or additionally over many assimilation cycles. Recently, the ECMWF have started to use (27) (averaging additionally over one month) to determine their B-matrix (replacing the NMC method) in the way described in Fisher and Andersson (2001), Fisher (2003) andŽagar, Andersson and Fisher (2005), and Météo-France ) use a similar ensemble-based method. Isaksen, Fisher and Berner (2007) have used the method to investigate flowdependent variances in the ECMWF system.…”
Section: The Ensemble (Monte Carlo) Methodsmentioning
confidence: 99%